2021
DOI: 10.2903/j.efsa.2021.6607
|View full text |Cite
|
Sign up to set email alerts
|

A systems‐based approach to the environmental risk assessment of multiple stressors in honey bees

Abstract: The European Parliament requested EFSA to develop a holistic risk assessment of multiple stressors in honey bees. To this end, a systems-based approach that is composed of two core components: a monitoring system and a modelling system are put forward with honey bees taken as a showcase. Key developments in the current scientific opinion (including systematic data collection from sentinel beehives and an agent-based simulation) have the potential to substantially contribute to future development of environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 174 publications
(224 reference statements)
0
20
0
Order By: Relevance
“… 29 , 31 A number of fungicide‐insecticide combinations have been shown to be synergistic, not just in laboratory bioassays, 30 but also under field conditions, 53 rendering mixture toxicity a topic of regulatory concern. 30 , 54 The strength of the synergistic potential of propiconazole in combination with CPR in a laboratory worst‐case scenario on both honey bee larvae and adults suggests that mixture toxicity under applied conditions cannot be excluded and possibly warrants scrutiny. 27 Our molecular study unveiled two known honey bee P450 isoforms possibly driving the observed synergism, thus allowing the use of a recently described molecular risk assessment approach.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 31 A number of fungicide‐insecticide combinations have been shown to be synergistic, not just in laboratory bioassays, 30 but also under field conditions, 53 rendering mixture toxicity a topic of regulatory concern. 30 , 54 The strength of the synergistic potential of propiconazole in combination with CPR in a laboratory worst‐case scenario on both honey bee larvae and adults suggests that mixture toxicity under applied conditions cannot be excluded and possibly warrants scrutiny. 27 Our molecular study unveiled two known honey bee P450 isoforms possibly driving the observed synergism, thus allowing the use of a recently described molecular risk assessment approach.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, EFSA has addressed this issue in the bee health area through a scientific opinion illustrating a refined approach to assess combined exposure to multiple chemicals, as well as biological agents (e.g., Varroa, Nosema, deformed wing virus and acute bee paralysis virus), nutrition and beekeeping management practices, as well as environmental factors relevant to the colony (e.g., weather and floral resources). Overall, the modelling system is based on the development of ApisRAM as an agent-based simulation model allowing single chemicals, multiple chemicals and multiple stressors to be assessed at the individual and population level [ 115 ].…”
Section: Future Challenges Recommendations and Conclusionmentioning
confidence: 99%
“…The first one reflects the need to develop more holistic approaches, allowing a move towards landscape modelling and systems-based approaches while integrating data at different levels of biological organisation (molecular, individual, species, population, ecosystem and landscape). The second major challenge requires the development of methods allowing RA of multiple stressors, integrating data for chemicals, emerging pathogens, invasive species and climate change, as demonstrated for honey bees and amphibians [ 115 ].…”
Section: Future Challenges Recommendations and Conclusionmentioning
confidence: 99%
“…Moreover, there is no optimal risk assessment method currently available for amphibians (and reptiles), despite a recognized vulnerability to PPPs (EFSA PPR Panel, 2018b). Similarly, no model related to bees was found, although the ApisRAM model (EFSA Scientific Committee et al, 2021) is under development and should be implemented in assessment reports in a near future.…”
Section: Non-target Organisms Addressed By Modellingmentioning
confidence: 99%
“…EFSA, 2009). Moreover, in the last decades, several publications supported the implementation of more sophisticated models in PPP regulation by providing guidance on good modelling practices (EFSA PPR Panel, 2014), pointing out among many other things the interest of toxicokinetic-toxicodynamic (TKTD) mechanistic models (EFSA PPR Panel, 2018a) or population models for bees (e.g., ApisRAM (EFSA Scientific Committee et al, 2021) or BEEHAVE (EFSA PPR Panel, 2015b)), reptiles and amphibians (EFSA PPR Panel, 2018b) as well as small mammals like common vole (Schmitt et al, 2016) with possible integration of variables at the landscape scale (e.g., ALMaSS model, Animal, Landscape and Man Simulation System, Topping et al, 2003). As a general rule, the ERA of PPP is continuously improving as demonstrated by the EFSA on-going reflection publication (EFSA, 2018).…”
Section: Introductionmentioning
confidence: 99%